Functional Characterization of Bacterial Communities Responsible for Fermentation of Doenjang: A Traditional Korean Fermented Soybean Paste - Jung, Woo Yong; Jung, Ji Young; Lee, Hyo Jung; Jeon, Che Ok (Frontiers in Microbiology, 2016)
Doenjang samples were prepared in triplicate and their microbial abundance, bacterial communities, and metabolites throughout fermentation were analyzed to investigate the functional properties of microorganisms in doenjang. Viable bacterial cells were approximately three orders of magnitude higher than fungal cells, suggesting that bacteria are more responsible for doenjang fermentation. Pyrosequencing and proton nuclear magnetic resonance spectroscopy were applied for the analysis of bacterial communities and metabolites, respectively. Bacterial community analysis based on 16S rRNA gene sequences revealed that doenjang samples included Bacillus, Enterococcus, Lactobacillus, Clostridium, Staphylococcus, Corynebacterium, Oceanobacillus, and Tetragenococcus. These genera were found either in doenjang-meju or solar salts, but not in both, suggesting two separate sources of bacteria. Bacillus and Enterococcus were dominant genera during the fermentation, but their abundances were not associated with metabolite changes, suggesting that they may not be major players in doenjang fermentation. Tetragenococcus was dominant in 108 day-doenjang samples, when lactate, acetate, putrescine, and tyramine increased quickly as glucose and fructose decreased, indicating that Tetragenococcus might be primarily responsible for organic acid and biogenic amine production. Lactobacillus was identified as a dominant group from the 179-day samples, associated with the increase of γ-aminobutyric acid (GABA) and the decrease of galactose, indicating a potential role for this genus as a major GABA producer during fermentation. The results of this study clarified the functional properties of major bacterial communities in the doenjang fermentation process, contributing to the production of safe and high-quality doenjang.